Intellectual property rights, foreign direct investment and economic growth - Palaniaandy, Ayappan; Lee, Chin (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
The objective of this study is to investigate the moderating role of IPR on the impact of FDI inflows on economic growth. By include an interaction term for FDI and IPR in each model, Two-step System GMM was applied for three proxies of IPR, namely patent, trademark and industrial design on a panel of 103 countries from 1998 to 2013. The result shows that interaction between FDI-trademark and FDI-design obtained a positive and significant result towards economic growth. It can be concluded that countries with high IPR’s could enhance their economic growth via higher inflows of FDI. A strict enforcement of IPR is vital in ensuring positive impact on economic growth as investors preferably place the FDI in a safe and secure nation that promises enforcement of law against imitation.